2020
DOI: 10.1590/1678-992x-2018-0166
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical properties and soil organic carbon content in northeast Brazil: long-term tillage systems effects

Abstract: Concerns about the negative effects of agriculture on soil physical quality and soil organic carbon (SOC) pools have spurred on the adoption of conservation tillage systems in tropical regions. This study aimed to evaluate the long-term impacts (16 th year) of conventional (CT), minimum (MT) and no-tillage (NT) practices and different cover crops (sunn hemp and a bean/ millet sequence) on soil physical properties and SOC content of a corn cultivated Ultisol in the northeast of Brazil. Soil bulk density (Bd), s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
1
22
0
1
Order By: Relevance
“…However, no clear trends were observed between different cropping patterns. Similarly, Oliveira et al [37] found no significant difference between beans and millet intercropping effects on Db.…”
Section: Bulk Densitymentioning
confidence: 91%
“…However, no clear trends were observed between different cropping patterns. Similarly, Oliveira et al [37] found no significant difference between beans and millet intercropping effects on Db.…”
Section: Bulk Densitymentioning
confidence: 91%
“…Residues of CC plants, including legume CCs, improve soil structure by influencing soil strength, porosity and hydraulic properties. They also increase the diffusion capacity of soil air, as well as the formation of soil aggregates (basic units of soil structure) [217][218][219] (Table 3). [222] no legume CCs mixture of S. cereale L., P.…”
Section: Effect Of Legume Ccs On Soil Structure and Aggregationmentioning
confidence: 99%
“…In fact, the green manure practice has the ability to change both soil physical and chemical soil properties due to the high biomass production on soil surface (e.g., at this point the green manure plants act as cover crops protecting soil surface from erosion) and their biomass incorporation into soil pro le (e.g., here promoting rhizodeposition, nutrient cycling), thus resulting in a healthy soil environment from the subsequent annual plant species (Pacheco et al 2017;Hirte et al 2018;Çerçioğlu et al 2019;Oliveira et al 2020;Hu and Chabbi, 2021;Liu et al 2021;Mortensen et al 2021). Our results highlight the importance of considering the green manure practice as an alternative way to input organic resources (Haruna et al 2020).…”
Section: Discussionmentioning
confidence: 99%